'To all who live in it' : an investigation of the dilemmas of, and prospects for, inclusive citizenship in South Africa - Schwartz, Carrie (Department of Political Studies, 2015)
This study is a literature-based analysis of the prospects for inclusive citizenship in light of the contradiction between formal political equality and the reality of socio-economic inequality within the context of post-apartheid South Africa. In approaching the topic of citizenship, I will employ T.H. Marshall's conceptual framework of three-fold citizenship to establish the civil, political and social elements and associated sets of rights within citizenship.